Profile of patients assessed for cochlear implants - Barbosa,Maria Helena de Magalhães (2014)
INTRODUCTION: Knowledge of the characteristics related to profound hearing loss is a matter of great importance, as it allows for the etiological and prognostic identification and strategic planning for public health interventions. OBJECTIVE: To assess the different etiologies of hearing loss, age at diagnosis of the hearing loss, its relation to language acquisition, and the age at the first consultation in this service for cochlear implant assessment. METHODS: This was a historical cohort, cross-sectional study, using retrospective analysis of the records of 115 patients with confirmed sensorineural hearing loss, who were followed in a university hospital, based on gender, age of hearing loss, age at the first consultation, language, and hearing loss etiology. RESULTS AND CONCLUSION: The majority of patients assessed for cochlear implants attend the first consultation when they are older than one year (an alarming mean of 3.8 years in the prelingual group) in spite of the early diagnosis of hearing loss. This reflects an already deficient health care system, in terms of referral. The idiopathic cause remains the most frequently identified. Among the known causes, the most prevalent are perinatal causes and meningitis.